2022
DOI: 10.1186/s12889-021-12429-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and the associated factors of hepatitis B and hepatitis C viral infections among HIV-positive individuals in same-day antiretroviral therapy initiation program in Bangkok, Thailand

Abstract: Background Viral hepatitis is highly prevalent among people with HIV (PWH) and can lead to chronic liver complications. Thailand started universal hepatitis B vaccination at birth in 1992 and achieved over 95% coverage in 1999. We explored the prevalence of hepatitis B and C viral infections and the associated factors among PWH from same-day antiretroviral therapy (SDART) service at the Thai Red Cross Anonymous Clinic, Bangkok, Thailand. Methods We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
3
2
Order By: Relevance
“…This finding explains why this study's monitoring/evaluation of HIV/AIDs prevention programmes suggested a high extent. The findings, however, contradict other studies that documented that the rising frequency of sexually transmitted illnesses, especially HIV/AIDS, demonstrates that previous attempts to combat the pandemic have been insufficient, even with antiretroviral therapy (Kalichman, Eaton, and Kalichman 2021;Mosha et al 2022;Jing et al 2022;Thitipatarakorn et al 2022). The disparity in results might be related to variations in the factors included in the investigations.…”
Section: Discussion Of Findingscontrasting
confidence: 83%
“…This finding explains why this study's monitoring/evaluation of HIV/AIDs prevention programmes suggested a high extent. The findings, however, contradict other studies that documented that the rising frequency of sexually transmitted illnesses, especially HIV/AIDS, demonstrates that previous attempts to combat the pandemic have been insufficient, even with antiretroviral therapy (Kalichman, Eaton, and Kalichman 2021;Mosha et al 2022;Jing et al 2022;Thitipatarakorn et al 2022). The disparity in results might be related to variations in the factors included in the investigations.…”
Section: Discussion Of Findingscontrasting
confidence: 83%
“…Anti-HCV positivity was found in 4-5% of PWH who were MSM and TGW. As World Health Organization and Thailand national guidelines already support routine screening of hepatitis B and C viral infections in PWH and populations at increased risk of HIV including MSM and TGW, healthcare providers should reinforce this strategy [2]. These findings were higher than the present study, which can be due to differences in viral hepatitis risk factors, different cultures and sample size.…”
Section: Discussioncontrasting
confidence: 79%
“…The name of this new disease was AIDS. More than 70 million people have been infected with HIV [2]. Ninety percent of HIV infections are in developing countries and Eighty percent are sexual transmission from men who have sex with men (MSM).…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, this prevalence is up to 6.9% in some provinces 3 . The prevalence of HCV co‐infection with human immunodeficiency virus (HIV) in Thailand is 4.1% 4 and as high as 77.6% in patients with HIV and history of intravenous drug usage 5 . HCV infection in HIV‐positive patients leads to aggressive liver diseases with advanced fibrosis and earlier progression to end‐stage liver diseases 6–8 .…”
Section: Introductionmentioning
confidence: 99%